A case study on the use of a conceptual modeling framework for construction simulation. (May 2022) - Abdelmegid, Mohammed Adel; O'Sullivan, Michael; González, Vicente A; Walker, Cameron G; Poshdar, Mani
Construction simulation has been an active area of research in the last six decades. Nevertheless, there has been a gap between academia and industry in realizing the capabilities of simulation to support decision-making in construction. One of the well-recognized reasons is the difficulty of undertaking comprehensive simulation studies by construction practitioners, who usually lack sufficient knowledge and skills to adequately build simulation models. Efforts to bridge this gap have been focused on simplifying the computer coding and model implementation stages of construction simulation studies with limited research on the early stage of defining the model and abstracting the system, i.e., conceptual modeling. The conceptual modeling stage is known to be one of the most difficult tasks in a simulation study. Thus, several frameworks to support building conceptual models have been proposed in simulation literature. This study contributes to the research efforts to promote simulation in the construction industry through the adoption of a conceptual modeling framework. It demonstrates the application of the proposed conceptual modeling framework in a case study of piling operations. The findings of this paper reinforced the significance of conceptual modeling by confirming the role of the conceptual model as a communication link between stakeholders. Moreover, the conceptual model was used as a specification document for developing a flexible model that can be replicated in other settings. The use of a documented conceptual model assisted in managing the overall simulation study efficiently, which, in turn, lead to reductions in time and effort for different modeling activities.